Welfare dynamics in rural Viet Nam: Learning from regular, high-quality panel data - Andrew D. McKay; Saurabh Singhal; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
While many studies of welfare dynamics have been conducted using panel data sets with two or three waves, much richer insights can be obtained where more waves are available. This paper analyses this issue for the case of the Viet Nam Access to Resources Household Survey, a carefully collected and high-quality data set collected over a period of eight years from 2008 to 2016. The survey was conducted over a period of impressive overall welfare improvement, but the data set highlights significant heterogeneity in this with significant numbers of households in fact becoming worse off. A panel-based econometric analysis of the evolution of different measures of welfare identifies that there are strong dynamics in welfare for all three measures considered here, but that shocks and changes in household composition are very important drivers of changing welfare levels at the household level.
Keywords: D31; I31; O12; Q12; 330; welfare dynamics; panel survey; Viet Nam